Lipid metabolism - Beisiegel, Ulrike (Henry Stewart Talks, 2008)
Functions of lipids, Lipid absorption in the intestine, Intestinal sterol and fatty acid uptake, Intestinal chylomicron formation, Postprandial hyperlipidemia, Lipoprotein model, Major lipoproteins and apoproteins, Postprandial lipoprotein metabolism, Insulin as major postprandial hormone, Metabolism of adipose tissue, Nutritional lipids are also delivered to the bone, Chylomicron remnants deliver lipids and vitamin K to the bone, Hepatic lipid metabolism, What are the receptors responsible for CR uptake?, CR uptake into the liver, Hepatic lipoprotein pathways, Size of VLDL determines LDL size, Role of apo E in lipoprotein catabolism, Apo E polymorphism, Cellular cholesterol homeostasis, LDL receptor involved in cellular cholesterol homeostasis, Intracellular cholesterol regulated gene expression, 'Reverse cholesterol transport' by HDL, Lipid exchange proteins, Normal levels for plasmalipids, Dietary lipids